Antigenic properties of human lymphoblastoid interferons. - Dalton, B J (1979)
Most virus-induced human lymphoblastoid interferons examined contained variable proportions of the Le and F antigenic species described for human leukocyte interferon. The F species was not detectable in interferons liberated spontaneously from human lymphoblastoid cells in culture. Lymphoblastoid interferons differed considerably in their interaction with the same anti-interferon serum. Spontaneous interferons required approximately ten times less antibody for neutralization than interferon induced by virus in the same cultures or in Namalva cells. The findings suggest that either spontaneous interferons contain fewer inactive antibody-binding molecules than virus-induced lymphoblastoid interferons or the number and distribution of antibody-combining sites, and possibly other surface properties of the interferon molecule, may be influenced by the manner in which spontaneous and induced interferons egress from the cells.